The schistosomicidal activity of ethanolic extracts from branches, leaves, flowers and fruits of Handroanthus impetiginosus (Mart. ex DC.) Mattos (Bignoniaceae) plant and metabolic profile characterization by UPLC-ESI-QTOF analysis - D. L. Montagnini; A. Katchborian-Neto; M. P. M. Tahan; N. D. Oliveira; L. G. Magalhães; A. H. Januário; P. M. Pauletti; P. S. S. R. Cavallari; W. R Cunha; O. P. Araujo; M. G. Soares; M. S. Ferreira; et al. (Brazilian Journal of Biology, 2023)
Abstract Schistosomiasis, caused by Schistosoma mansoni Sambon, 1907, is a severe and widely distributed parasitic disease, affecting about 200 million people worldwide. The disease is recognized by elevated mortality rates, especially among those living in areas of poor sanitation. Currently, the chemotherapeutic treatment is solely based on using the praziquantel drug. Therefore, there is a need for the discovery of new medicines for the treatment of this parasitosis. Thus, this work aimed to evaluate the schistosomicidal activity of ethanolic crude extracts from the branches, leaves, flowers, and fruits of Handroanthus impetiginosus (Mart ex DC.) Masttos and characterize its metabolic profile by UPLC-ESI-QTOF analysis. Evaluation of plant extract on S. mansoni was carried out in adult worms in vitro, in which the mortality rate was quantified, and the damages in the tegument of the worms were monitored. All extracts induced changes in the viability of adult males of S. mansoni, causing the death of the parasites, which was directly dependent of the concentration.